2019
DOI: 10.3928/01477447-20181120-05
|View full text |Cite
|
Sign up to set email alerts
|

Bone Scintigraphy: A Review of Technical Aspects and Applications in Orthopedic Surgery

Abstract: Due to its high sensitivity, low cost, accessibility, and ease of use, bone scintigraphy is used in orthopedic surgery for the diagnosis and management of varied pathology. It is commonly used for insufficiency fractures, metastatic neoplasia, staging and surveillance of sarcoma, and nonaccidental trauma. It augments diagnoses, including stress or occult fractures, musculoskeletal neoplasia or infection, and chronic regional pain syndrome, in patients presenting with normal results on radiographs. Bone scan im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…[ 22 23 ] Even in the diagnosis of occult lesions, a bone scan with SPECT/CT is very helpful. [ 24 ] Krumme et al [ 25 ] in their study concluded that bone scan is an “underused tool” in the evaluation and management of orthopedic patients including those presenting with IFs and the authors concur with that.…”
Section: Discussionmentioning
confidence: 88%
“…[ 22 23 ] Even in the diagnosis of occult lesions, a bone scan with SPECT/CT is very helpful. [ 24 ] Krumme et al [ 25 ] in their study concluded that bone scan is an “underused tool” in the evaluation and management of orthopedic patients including those presenting with IFs and the authors concur with that.…”
Section: Discussionmentioning
confidence: 88%
“…In 99m Tc-MDP bone scintigraphy, the tracer uptake reflects the vascular supply of bone and the living network of osteocytes; thus, it was originally used to assess the properties of primary bone lesions 24 . Bone metastasis, recurrence, and postoperative complications of the bone, including infection, fracture, or nonunion, can also be detected by 99m Tc-MDP bone scintigraphy 25 . In addition, bone scintigraphy can be used to evaluate the viability of devitalized bone, because it is more sensitive for monitoring the revascularization and revitalization process, in comparison to roentgenography, CT, and MRI, especially in cases with ferromagnetic effects due to the use of composite implants 24 .…”
Section: Textmentioning
confidence: 99%
“…24 Bone metastasis, recurrence, and postoperative complications of the bone, including infection, fracture, or nonunion, can also be detected by 99m Tc-MDP bone scintigraphy. 25 In addition, bone scintigraphy can be used to evaluate the viability of devitalized bone, because it is more sensitive for monitoring the revascularization and revitalization process, in comparison to roentgenography, CT, and MRI, especially in cases with ferromagnetic effects due to the use of composite implants. 24 The postoperative course of incorporation and revascularization of pasteurized autografts, as well as extracorporeally irradiated autografts, has also been evaluated by bone scintigraphy.…”
Section: Textmentioning
confidence: 99%
“…Gallium 67 scintigraphy has higher specificity than does triple-phase bone scanning. Thus, these two examinations are often combined (5). Labeled leukocyte scintigraphy and fluorine 18 fluorodeoxyglucose PET/CT may be used to successfully diagnose spinal infection.…”
Section: Imagingmodalitiesmentioning
confidence: 99%